Superconducting and Elastic Properties of PbBa2Y1-xCaxCu3O7+δ - Chong, Tet Vui; Abd Shukor, Roslan (Trans Tech Publications Inc., 2016)
PbBa2Y1-xCaxCu3O7+δ (x = 0.00, 0.15, 0.20, 0.25 and 0.50) samples were prepared via solid state reaction. All samples except x = 0.50 exhibited various critical temperatures Tc. The X-ray diffraction patterns show all samples were in mixed phase. Longitudinal and shear ultrasonic velocities in these samples were measured using the pulsed-echo-overlap method with frequency 5-10 MHz in the temperature range 80-300 K. There are no obvious elastic anomalies which are usually observed in most high temperature superconductors were observed in any of the samples in both longitudinal and shear modes. Furthermore, there is no significant variation in the percentage of velocity change in both longitudinal and shear modes with the different content of x doped for all samples.